Clinical Profile and Outcome of Mechanically Ventilated Neonates In A Resource-Limited Neonatal Intensive Care Unit - Ashfaq, Raiha; Aatif, Muhammad; Basheer, Faisal; Iqbal, Amjad; Maqbool, Wajahat; Hamza, Ameer (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the clinical profile and outcome of mechanically ventilated neonates in a resource-limited neonatal intensive care unit. Study Design: Prospective longitudinal study. Place and Duration of Study: Department of Pediatrics Combined Military Hospital Sialkot Pakistan, from Apr to Sep 2022. Methodology: Records of 150 neonates admitted to our neonatal intensive care unit (NICU) who underwent mechanical ventilation within the specified period were reviewed. We recorded their gestational age, birth weight, mode of delivery, APGAR scores, maternal medical history, admitting diagnosis and the indication for mechanical ventilation. They were followed for duration of ventilation, complications and outcomes. Chi square test was used to check for association between the variables. Results: The most common indication for ventilation was severe respiratory distress with inability to maintain oxygenation in 104(69.33%) cases, followed by perinatal asphyxia with ineffective ventilation in 19(12.66%) cases. Notable associated conditions among ventilated neonates included sepsis in 57(38.00%) respiratory distress syndrome in 27(18.00%) and meconium aspiration syndrome in 18(12.00%) neonates. The frequency of survival for ventilated neonates was 52(34.66%). Conclusion: The predominant reason for initiating mechanical ventilation was severe respiratory distress with inability to maintain oxygenation. Sepsis was the most frequent condition associated with mechanical ventilation.